Search 74,241 tutors
FIND TUTORS

Shefali J.'s Resources

Answers

Hello Treena, For solving this question you need to use the slope formula. m = (y2 - y1)/(x2 - x1) Given to you are the coordinates of (x1, y1) and (x2, y2) and also the slope m. x1 = 5; y1 = y; x2 = 7, y2 = -9 and m = -4 Substitute these values in the slope formula and solve...

Answers

Hello Kaz, a. For the line to be parallel the slope of both lines have be same. The equation given to you is in standard form. So, first bring the equation in slope-intercept form. 3x + 4y = 7 -3x          -3x ________________ 4y...

Answers

Hello Kayla, Graph the first inequality y > -x - 2. Since, it has > than symbol use dashed line. Now, your graph is divided in two parts. For the easiest way to find out which side of the graph you need to shade pick origin(0, 0) as your checking point. Substitute x = 0 and y =...

Answers

Hello Robyn, Two equations given are  2x - 6y = -10 -------------->equation 1 4x = 10 + 6y -------------->equation 2 We'll solve this problem using the elimination method. Solve equation 2 4x = 10 + 6y (given) -6y        -6y  (subtract...

Answers
(m^2-5)(2 m^2+3) (answer)

Hello Jessica, Use FOIL method to multiply (m2 - 5)(2m2 + 3) m2(2m2 + 3) - 5(2m2 + 3) Now, distribute, combine like terms and solve you'll get your answers. I hope it helps you. If you need further assistance you can ask.

Answers

Hello Jessica, Multiply 6.32 and 9.5 Multiply 10-12 and 10-5using exponent rule (am * an = am+n) Combine your answer. If you need further help you can ask. Myself or any other tutor will help you.

Answers

Hello Connor, The constant term of this polynomial is 10, with factors 1, 2, 5, and 10. The leading coefficient is 2, with factors 1 and 2. Then the Rational roots yields the following possible solutions: ±(factors of 10)/(factors of 2) = ±(1, 2, 5, 10)/(1,2) = ±1/1, ±1/2, ±2/1, ±5/1, ±5/2, ±10/1 = ±1, ±1/2, ±2, ±5, ±5/2, ±10...

Answers

Hello Jen, Use the point-slope formula y - y1 = m(x - x1) Here, x1 = 1 , y1 = 2 and m = 1/2 So, after substituting you'll get y - 2 = (1/2) (x - 1) y - 2 = (1/2)x - (1/2)       (distribute 1/2) Add 2 on both sides of the equation y -...

Answers
2x-4/7=x-1/9 (answer)

Hello Rebecca, For this problem use the cross multiplication. Multiply (2x - 4) by 9 and (x - 1) by 7. Next, use distributive property and get rid of brackets, you'll get 18x - 36 = 7x - 7 Now you need to isolate the variable x. For that subtract 7x from both sides of the equation. You'll...

1 2 3